R&D Institutes in ECA : A Reform Strategy - Racine, Jean-Louis; Goldberg, Itzhak; Goddard, John Gabriel; Kuriakose, Smita; Kapil, Natasha (World Bank, Washington, DC, 2012)
In Eastern Europe and Central Asia (ECA) countries, the states own and operate most of the research and development institutes (RDIs). These institutes often play an important and even dominant role in conducting research and development (R&D). In high-income economies, however, the private sector typically dominates R&D. Private sector research usually responds better to market incentives, resulting in more useful innovations than public sector R&D, although the two are complementary. In general, the economic impact of RDIs in ECA has been low. Although several ECA RDIs are able to publish and patent as much as their high-income economy counterparts, the quality of their research and ability to diffuse knowledge is lagging and their international publications are not highly cited. In addition, their patents are not translated into commercial applications through licensing or contract research with industry. A reform strategy is proposed here for RDIs in ECA, based on their relevance to national priorities, expected role as providers of public versus private goods, performance levels, and relation to relevant markets and users. When deciding on the appropriate ownership and management structures for the RDIs, governments need to distinguish among RDIs that provide mainly public goods, RDIs that sell or could possibly sell mainly private goods and services, and RDIs that produce public and private goods.